Diagnóstico de la existencia y uso de la maquinaria agrícola en el cantón Baba, Provincia de Los Ríos en el año 2023 - Vera Mariscal, Kevin Raúl (2023)
This study was carried out in the Baba cantón of the province in Los Ríos, Ecuador; with the application of the type of descriptive, non-experimental research with the support of descriptive inferential statistics. where, through the survey methodology, the information regarding the use of agricultural machinery and implements in Production Units of short-cycle crops in the year 2023 was collected, which after being statistically processed allowed detailing the social aspects, such as gender, marital status and academic level of the producer; secondly, the agricultural technical aspects were described, such as the characterization, classification and establishment of reliability and finally, the degree of satisfaction with the use of existing agricultural machinery in the aforementioned canton was evaluated. It was determined that the short-cycle crops that are planted are mainly rice, followed by corn and soybeans. The agricultural machinery and implements used in the area are the tractor, combine harvester, walking tractor, boom sprayer, harrow, fertilizer spreader, plow, motorized backpack, motorized pump, roadheader and seeder with a very low level of technical advice; including that those with the highest use exceed 90% of rent, due to the fact that the surface of the production units is less than 5 ha or rented. Finally, it is determined that the producers are satisfied with the current cost of providing machinery services and for production work.